An analysis of resource conservation technology in improving farmer’s livelihood: A case of micro irrigation system - SACHAN, BANDANA; PATEL, NEELAM (Journal of Soil and Water Conservation, 2023)
The annual food grain requirement of India is estimated as 450 million tons by the year 2050 with the per capita availability of 760 m3 against the 6008 m3 in 1947 (presently 1250 m3). To meet the food security, income and nutritional needs of the projected population in 2050, the food production will have to be almost doubled. Management of water, may help in savings of significant amounts of water and increase the quality and quantity of produce. To solve totally, or to reduce, the severity of water scarcity, water management must improve at field level. Thus, agriculture has the greatest potential for solving the problem of water scarcity. With a view to addressing the above issues and to particularly increase the water use efficiency and productivity of vegetables at field level through micro irrigation, a study was taken up in the district Alwar, Rajasthan. Participatory Rural Appraisal techniques were conducted in the villages to get an insight in to the farmers’ perceptions. Total 2.5 ha area belonging to five farmers was placed under drip irrigation during 2012 and 2013, utilizing low discharge of tube wells which is not possible in flood irrigation in cotton and kharif onion. Fifteen (15) moveable Raingun sprinkler systems were installed for irrigation of wheat crop in the villages. Cotton under drip irrigation could save 50% (5120 m3 water under drip and 10240 m3 under flood) of water besides 75% enhance in yield (2.8 t/ha in drip against 1.6 t/ha in flood). Kharif onion under drip irrigation could save 40% (3388 m3 water under drip and 5646 m3 under flood) of water besides 50% enhance in yield (24 t/ha in drip against 16 t/ha in flood). Impact of this technology motivated other farmers of nearby villages and now many farmers are coming forward for the large scale adoption. Investment in micro irrigation also appears to be economically viable but both the villages were not having any micro irrigation systems. It is identified that slow spread of Micro irrigation is not mainly due to economic reasons and less awareness among the farmers about the real economic and revenue-related benefits of it.